2018
DOI: 10.1007/s11356-017-1187-4
|View full text |Cite
|
Sign up to set email alerts
|

Alternative soilless media using olive-mill and paper waste for growing ornamental plants

Abstract: Peat-based growing media are not ecologically sustainable and peat extraction threatens sensitive peatland ecosystem. In this study, olive-stone waste (OSW) and paper waste (PW) were used in different ratios-as growing media-for ornamental crop production, as peat (P) substitutes. Marigold (Calendula officinalis L.), petunia (Petunia x hybrita L.) and matthiola (Matthiola incana L.) plants were grown in (1) P (100%), (2) P:OSW (90%:10%), (3) P:OSW (70%:30%), and (4) P:OSW:PW (60%:20%:20%). The physicochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(58 citation statements)
references
References 49 publications
2
56
0
Order By: Relevance
“…These contrasting results could be attributed to the different growth substrates and growing systems implemented in these studies, as well as to the severity of salinity stress which was higher in the study of Klados and Tzortzakis (2014). Higher values of total phenolic compounds content were also reported for parsley and dill plants grown in Germany soil in comparison to peat-based substrates by Saleh et al (2019), while Chrysargyris et al (2018a) demonstrated the effect of using paper in growth substrate blends on total phenols content of ornamental plants. In contrast, Dannehl et al (2015) reported no significant differences in total phenolic compounds in fruit of tomato plants grown in peat moss, rock wool, sheep wool and hemp which indicates that there is also a species depended response to growth substrate.…”
Section: Effect Of Growth Substrate On Phenolic Compounds Profilementioning
confidence: 79%
See 1 more Smart Citation
“…These contrasting results could be attributed to the different growth substrates and growing systems implemented in these studies, as well as to the severity of salinity stress which was higher in the study of Klados and Tzortzakis (2014). Higher values of total phenolic compounds content were also reported for parsley and dill plants grown in Germany soil in comparison to peat-based substrates by Saleh et al (2019), while Chrysargyris et al (2018a) demonstrated the effect of using paper in growth substrate blends on total phenols content of ornamental plants. In contrast, Dannehl et al (2015) reported no significant differences in total phenolic compounds in fruit of tomato plants grown in peat moss, rock wool, sheep wool and hemp which indicates that there is also a species depended response to growth substrate.…”
Section: Effect Of Growth Substrate On Phenolic Compounds Profilementioning
confidence: 79%
“…Biochar is also a candidate substrate for soilless cultivation of leafy vegetables since research studies demonstrated that its use increased plant growth and mineral composition and decreased the undesirable growth of algae in nutrient solution (Awad et al, 2017). Other potential peat substitutes include composts from distillery wastes (Bustamante et al, 2008), mixtures of vegetable waste, manure and sawdust (Gavilanes-Ter an et al, 2016), paper waste (Chrysargyris et al, 2018a), hazelnut husks (Dede et al, 2011), and sawdust (Marinou et al, 2013) among others.…”
Section: Introductionmentioning
confidence: 99%
“…The scavenging of ROS is then directly linked to the activity of antioxidant enzymes, such as SOD, POD, and CAT. The activities of these enzymes generally increase with the increase in stress severity [9,60,61]. Furthermore, reducing power was also not altered significantly in response to either BC or BioComp amendment (Table 7).…”
Section: Biochemical Parametersmentioning
confidence: 93%
“…In Europe, the volume of organic substrate used for the nursery sector amounts to 34.6 million m 3 per annum, of which 27 million m 3 is composed of peat [7]. The use of peat as growing media, however, has caused ecological concerns [8] because peat is a non-renewable resource, and peatland is a sink of carbon dioxide [9,10]. As a result, peat has become costlier for commercial use [5,11], and there is an increasing need for alternative organic materials to replace or partially replace peat for the production of container plants [5,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation